From Ruins and Ashes…: The Interaction between the USSR and the Allies in the Field of Architecture during the Second World War - Vyasemtseva, Anna G.; Malich, Ksenia A.; Pechenkin , Ilia E. (Actual Problems of Theory and History of Art, 2023)
The article examines the history of contacts between the USSR, Great Britain, and the USA in the architectural field during the World War II. Along with military, political, and logistical cooperation, there was a cultural exchange between the countries participating in the Anti-Hitler coalition, but it was in the field of architecture where the theoretical and practical aspects were firmly connected. The abundance of printed materials and archival documents testifies to the mutual interest of Soviet and Western architects in each other's problems and achievements. However, there was quite a certain pragmatism behind this activation of contacts. Publications addressed to Western partners and entire traveling exhibitions reporting on the colossal damage inflicted on Soviet territory by the war allowed to determine the contours of possible cooperation. Soviet architects and officials were interested in importing the approaches to the restoration of destroyed objects, constructive solutions, and building technologies. In particular, the experience of the United States in the field of urban planning and housing construction, including the production of prefabricated houses, was studied in detail. The allies (primarily the Americans), for their part, viewed the USSR as a potential market for their manufacturers. The implementation of these mutually beneficial intentions proved impossible due to the sharp cooling in the relations between the Western Allies and the USSR immediately after the end of World War II. The former actors of professional interaction turned out to be under suspicion in their own countries. The Soviet ones, who were accused of worshiping the West, had to pay a particularly cruel price.The article is prepared in the framework of research project № 21-51-15002, funded by RFBR.
Keywords: architecture; 20th century; WWII; Allies; international connections; VOKS; Union of Soviet Architects